Stepwise surgical approach to diabetic partial foot amputations with autogenous split thickness skin grafting. Issue 1 (1st January 2016) - Ramanujam, Crystal L.; Zgonis, Thomas
Abstract : In the surgical treatment of severe diabetic foot infections, substantial soft tissue loss often accompanies partial foot amputations. These sizeable soft tissue defects require extensive care with the goal of expedited closure to inhibit further infection and to provide resilient surfaces capable of withstanding long-term ambulation. Definitive wound closure management in the diabetic population is dependent on multiple factors and can have a major impact on the risk of future diabetic foot complications. In this article, the authors provide an overview of autogenous skin grafting, including anatomical considerations, clinical conditions, surgical approach, and adjunctive treatments, for diabetic partial foot amputations.